Influence of milling methods on the flow properties of ivory teff flour. Issue 6 (20th September 2021) - Barretto, Roselle; Buenavista, Rañia Marie; Pandiselvam, Ravi; Siliveru, Kaliramesh
Abstract: Increasing teff ( Eragrostis tef) consumption has been recorded in recent years due to its gluten‐free nature and exceptional nutritional composition. Studies on the particle level that relates to processing and handling of teff flour are limited. The effect of different milling methods (roller mill, pin mill, and hammer mill) on size distribution, shape characteristics, and flowability of teff flour was evaluated. Physical properties (angle of repose, tapped and bulk densities, size distribution, and shape characteristics) and proximate composition were investigated and correlated with flow properties. Flowability was measured in terms of bulk, shear, and dynamic flow properties using the FT4 powder rheometer. Particle size distribution significantly ( p  < .05) influenced the angle of repose, aeration energy, and wall friction angle while shape characteristics (circularity and aspect ratio) significantly ( p  < .05) affected the aerated and tapped bulk densities and basic flow energy. Hammer‐milled flour had the highest aerated (548.00 kg/m 3 ) and tapped bulk densities (804.33 kg/m 3 ). Pin‐milled flour had the highest compressibility index (38.46%), Hausner ratio (1.62), angle of repose (71.57°), and wall friction angle (25.92° at 3 kPa) indicating poorer flowability. Stability index and specific energy did not vary significantly ( p  > .05) among the milled flours. Highest basic flow (1, 191.03 mJ) and aerated energies (272.32 mJ) were required to induce flow in hammer‐milled flour due to greater proportion of large particles. Based on the flow function, all flours fall under the "easy flowing" category, but the pin‐milled flour exhibited the poorest flowability. Abstract : Ivory teff grains were milled in roller, pin, and hammer mills to determine the effect of milling methods on flow properties, particle size and distribution, and shape characteristics. Based on the flow function, all flours fall under the "easy flowing" category, but the pin‐milled flour exhibited the poorest flowability. Particle size distribution significantly influenced the angle of repose, aeration energy, and wall friction angle while shape characteristics significantly affected the aerated and tapped bulk densities, and basic flow energy.